A new bioactive cembranoid sarcophytonolide V from Bornean soft coral genus Sarcophyton - Kazuki Tani; Takashi Kamada; Phan, Chin Soon; Charles S. Vairappan (2019)
A new cembranolide diterpene, sarcophytonolide V (1), along with 6 known compounds, isosarcophytonolide D (2), (4Z,8S*,9R*,12E,14E) -9-hydroxy-1- (prop-1-en-2-yl) -8,12- dimethyl- oxabicyclo[9.3.2]-hexadeca-4,12,14-trien-18-one (3), (7E,11E)-3,4-epoxy-7,11, 15- cembratriene (4), (1S*,3S*,4S*,7E,11E)-3,4-epoxy-13-oxo-7,11,15-cembratriene (5), (-) -eunicenone (6), and 2-[(E,E,E)-7′, 8′-epoxy-4′,8′,12′ -trimethylcyclotetradeca- 1′,3′,11′- trienyl] propan-2-ol (7) were isolated from the Bornean soft coral Sarcophyton sp. Their structures were elucidated based on spectroscopic data, such as nuclear magnetic resonance (NMR) and high resolution electron spray ionization mass spectroscopy (HRESIMS). These compounds were evaluated for their biological activity against marine pathogenic fungi.